K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

ngu thế

4 tháng 1 2019

2^8:2^4=2^4=8

23 tháng 10 2017

\(4.2^3:3^3+25^2:5^2\)

\(=4.8:27+5^4:5^2\)

\(=\frac{32}{27}+25\)

\(=\frac{707}{27}\)

3 tháng 2 2016

a,(x+2)(x-2)-(x-3)(x+1) 
= x^2 - 2^2 - ( x^2 + x - 3x - 3 ) 
= x^2 - 4 - x^2 - x + 3x +3 
= 2x -1

duyệt đi olm

 

3 tháng 2 2016

sorry moi hc lop 5

20 tháng 6 2017

\(8^2.2.2^3\)

\(=\left(2^3\right)^2.2.2^3\)

\(=2^6.2.2^3\)

\(=2^{10}\)

\(=1024\)

20 tháng 6 2017

=64x2x8=128x8=1024